Asphalt Plant - Schmitt Robert L. (McGraw-Hill's AccessEngineering., 2018)
This video identifies asphalt plant as machines that blend, heat, and mix aggregates and asphalt cement to produce asphalt concrete. It focuses on drum-mixed plants that produce hot-mixed asphalt. It shows in detail the different parts and opera